Hubungan antara motivasi belajar dan disiplin belajar dengan keterampilan berpikir kritis ips materi interaksi manusia dengan lingkungan dan pengaruhnya pada anak didik kelas v. - Nunung Lusiana; Jenny Indriastoeti Siti Poerwanti; Matsuri Matsuri (Didaktika Dwija Indria, 2021)
The purpose of this research is to find out the correlation between motivation and learning discipline with critical thinking skills. The respondents of this research are 85 students of 5th grade from three elementary schools in Kranggan district. This research is correlational quantitative research. Data collected by using test techniques for critical thinking skills. As for the motivation and learning discipline, the data is collected by using non-test techniques. The validity of the questionnaire is obtained using content validity. In calculating the final results, it is found that the correlation between independent variable, learning motivation, and the dependent variable, critical thinking skills result in such a low category of 0,372. The effective contribution of learning motivation to critical thinking skills is 11,5% and the relative contribution is 56,3%. Whereas, the correlation between independent variable, learning discipline, and the dependent variable, critical thinking skills, the strength of the correlation is low, which is equal to 0,337. The effective contribution of learning discipline  to critical thinking skills is 8,9% and the relative contribution is 43,6%. The contribution of motivation and learning discipline to critical thinking skills simultaneously is 20.5% through multiple regressions with the results of Sig. F change of 0.000> 0.05